Case Report: Collision tumors of the sellar region: pituitary adenoma and chordoma coexist in the sellar region - Shuo Gao; Pule Liu; Shude Yang; Kai Liu; Zhiqiang Zhao; Yadong Wang; Qiang Li; Jinqian Dong (Frontiers in Endocrinology)
Collision tumors are relatively rare and refer to the coexistence of distinct tumors in the same anatomical region, where they invade each other. Sellar collision tumors are especially uncommon. Recent studies suggest that most cases involve the coexistence of pituitary adenomas and craniopharyngiomas, whereas collision tumors comprising pituitary adenomas and chordomas are exceedingly rare. To the best of our knowledge, this case represents the fourth reported instance of an intrasellar chordoma coexisting with a pituitary adenoma. This case report presents a 60-year-old male patient with a collision tumor consisting of a sellar chordoma and a pituitary adenoma. Enhanced MRI identified a large space-occupying lesion involving the sellar region, suprasellar area, and third ventricle, suspected to be a soft tissue chordoma. Histopathological examination following endoscopic transnasal surgery confirmed the diagnosis of a sellar chordoma coexisting with a pituitary adenoma. This case offers valuable insights into the clinical manifestations and imaging characteristics of sellar chordoma coexisting with pituitary adenoma, contributing to a better understanding of this rare condition. Furthermore, this article reviews the existing literature, serving as a reference for the diagnosis and management of such conditions.